2013
DOI: 10.14233/ajchem.2013.13338
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Azabicyclo[3.1.0]amine Analogues of Anacardic Acid as Potent Antibacterial Agents

Abstract: Azabicyclo[3.1.0]amine analogues of anacardic acid (16a, 16b, 18a, 18b, 19 and 19b) were synthesized from anacardic acid and tested for their antibacterial activity against Gram positive and Gram negative bacteria. Most of the compounds are having potency at par with ampicillin and inferior with other standard drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A series of benzyl amine derivatives of anacardic acid ( 18a – v ) [ 59 ] have been developed ( Figure 6 ) from anacardic acids and assayed for activity against both gram-negative ( E. coli and P. aeruginosa ) and gram-positive bacteria ( S. aureus and S. pyogens ) and compared with standard ampicillin, chloramphenicol, ciprofloxacin, and norfloxacin [ 59 ]. The results revealed that none of the synthesized anacardic acids was superior to standard antibiotics against all tested bacteria.…”
Section: Anacardic Acids As Synthons For Synthesis Of Biologicallymentioning
confidence: 99%
“…A series of benzyl amine derivatives of anacardic acid ( 18a – v ) [ 59 ] have been developed ( Figure 6 ) from anacardic acids and assayed for activity against both gram-negative ( E. coli and P. aeruginosa ) and gram-positive bacteria ( S. aureus and S. pyogens ) and compared with standard ampicillin, chloramphenicol, ciprofloxacin, and norfloxacin [ 59 ]. The results revealed that none of the synthesized anacardic acids was superior to standard antibiotics against all tested bacteria.…”
Section: Anacardic Acids As Synthons For Synthesis Of Biologicallymentioning
confidence: 99%
“…Occasionally, the same conversion starting from enyne analogues has also been achieved by a photocatalytic pathway [34][35][36] as well as metal-free organocatalytic processes [37][38][39][40][41][42], mechanisms that are similar to the metal carbene processes (Scheme 1a). Another two effective approaches for the synthesis of 3-azabicyclo[3.1.0]hexanes involve the derivatization reactions of substituted cyclopropanes, such as C(sp 3 )-H bond activated alkenylation/amination tandem reactions and intramolecular aminolysis reactions Molecules 2023, 28, 3691 2 of 15 (Scheme 1b) [43][44][45][46][47][48][49][50][51][52][53], and the reaction of functionalized maleimide derivatives with one carbon donor generated in situ derived from substituted diazomethanes, bromo(nitro)methane, substituted α-diazoacetates, and N-tosylhydrazones via an intermolecular [2+1] fusedannulation reaction (Scheme 1c) [54][55][56][57][58][59][60][61][62][63][64]. In particular, the base-induced intramolecular spirocyclization method of the alkylation subunit precursor appeared to be a more efficient proprietary reaction to access 3-azabicyclo[3.1.0]hexane scaffold-containing natural products via aryl metal or radical dearomatization/cyclization reactions (Scheme 1d) [65][66][67][68][69][70][71]…”
Section: Introductionmentioning
confidence: 99%